2008
DOI: 10.1124/mol.108.052589
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA Methylation and Histone Modification Profiles of Liver-Specific Transporters

Abstract: Tissue-specific expression of transporters is tightly linked with their physiological functions through the regulation of the membrane transport of their substrates. We hypothesized that epigenetic regulation underlies the tissue-specific expression of mouse liver-specific transporters (Oatp1b2/ Slco1b2, Ntcp/Slc10a1, Bsep/Abcb11, and Abcg5/g8). We examined their DNA methylation and histone modification profiles near the transcriptional start site (TSS) in the liver, kidney, and cerebrum. Genome-wide DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…The degree of DNA methylation in these regions was calculated and compared among the tissues (Table 1). The corresponding data for Oatp1b2 were cited from our previous study (Imai et al, 2009) for comparison. In Oatp1c1, one CpG site located at +149 relative to the TSS was regarded as T-DMR, and the other 2 sites upstream of the TSS were similarly methylated among tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The degree of DNA methylation in these regions was calculated and compared among the tissues (Table 1). The corresponding data for Oatp1b2 were cited from our previous study (Imai et al, 2009) for comparison. In Oatp1c1, one CpG site located at +149 relative to the TSS was regarded as T-DMR, and the other 2 sites upstream of the TSS were similarly methylated among tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In various types of genes, the widespread existence of tissue-dependent differentially methylated regions (T-DMRs) around their transcription start sites (TSS) has been described, which can potentially explain tissue-specific expression of respective genes (Shiota et al, 2002;Yagi et al, 2008). Recently, we and others have demonstrated an association of DNA methylation with the tissue-specific expression of human and mouse transporters (Aoki et al, 2008;Imai et al, 2009;Jin et al, 2012;Kikuchi et al, 2007;Kikuchi et al, 2006;Kikuchi et al, 2010). In particular, genome-wide DNA methylation analysis using a methylation-sensitive restriction enzyme HpyCH4IV and mouse promoter tiling array revealed that 53 of 297 SLC transporter genes in mouse, including Oatp1b2/Slco1b2, were associated with T-DMRtags in the liver (Imai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that DNA methylation-dependent gene silencing underlies the kidney-specific expression of human OAT3 and mouse Urat1 (Kikuchi et al, 2006(Kikuchi et al, , 2007. Subsequently, a genomewide DNA methylation analysis together with bioinformatics approaches located tissue-dependent differentially methylated regions (T-DMRs) that were hypomethylated in the liver but hypermethylated in the extrahepatic tissues in a number of liver-specific genes, including transporters, and many of those genes contained HNF1-binding sequences in their promoters (Yagi et al, 2008;Imai et al, 2009). Most recently, we also identified T-DMRs in the kidney-specific amino acid transporters that are potentially transactivated by Hnf1␣/␤ (Kikuchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%